Oregano, thyme and sage, as natural additives to foods - SOLOMAKOS (Ν. ΣΟΛΩΜΑΚΟΣ) N.; GOVARIS (Α. ΓΚΟΒΑΡΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Herbs have been used as natural additives against chemical additives during the last few years, since the latter have been accused that can endanger consumers life. Oregano (Origanum vulgare ssp hirtum), thyme (Thymus vulgaris) and sage (Salvia officinalis) are three herbs that are found in Greece and their use as natural additives to foods have been investigated in recent years all over the world. Herbs are rich in phenols, which are principally characterized by a notable antimicrobial and antioxidative activity. The two main phenols of Oregano and thyme are carvacrol and thymol, which are in higher amounts than other compounds. The main phenolic compounds of sage are thusone and rosmanol. Other compounds found in lower amounts, like n-cymene (in Oregano and thyme) or a-terpineol (in sage) contribute in the antimicrobial and antioxidative activity of these herbs. Oregano, thyme and sage present an important antimicrobial activity against several pathogens of foods, such as Staphylococcus aureus, E. coli, E. coli 0157:H7, Salmonella typhimurium, Yersinia enterocolitica, Campylobacter jejuni or Listeria monocytogenes. The present herbs present also an important antifungal activity against fungi that can grow in foods like Aspergillus spp. or Candida spp., which can endanger consumers life. The antimicrobial and antioxidative activity of these herbs was verified either in vitro experiments or in foods. The dietary supplementation of Oregano and thyme essential oil to chicken and turkeys resulted in the oxidative stability of their meat during refrigerated and frozen storage.